COLLECTIVE MANIFESTATION OF EUROSCEPTIC PARTIES AND GROUPS CRITICAL IDEAS IN EUROPEAN UNION TREATIES - Palupi Anggraheni; Chitra Regina Apris (Jurnal Studi Diplomasi dan Keamanan, 2021)
The withdrawal of the United Kingdom from the European Union (EU) increases awareness of how far the Euroscepticism ideas spread among EU's members. As one of the pivotal EU members, the UK's withdrawal will bring consequences, especially how other countries' members perceived this action. The research focuses on how far the Eurosceptic party's critical ideas are manifested in the European Union treaties. This type of research is descriptive and qualitative. The scope of this research will focus on the Euroscepticism parties and movements in Austria, France, Italy, Netherland, and the United Kingdom. In this study, the authors use the concept of Euroscepticism to explain the classification of parties into the Euroscepticism Hard and Soft category and Neil J. Smelser's Value-Added Collective Behaviour scheme to describe the determinants of their collective action against the European Union. The result of this research is that Euroscepticism spreads throughout Europe by manifesting their critical ideas through six determinants factor, such as structural conduciveness, structural tension, growth, and spread of general beliefs, trigger factors, participant mobility, and social control. The manifestation of critical ideas carried out by Euroscepticism parties in the three countries can be seen through the Single European Act, Maastricht Treaty, Treaty Establishing Constitution for Europe, Referendum British Exit. The culmination of collective action by the Eurosceptic parties was the launch of EU critical campaigns (No to EU!) As well as a significant vote in the EU parliamentary elections.